Design and Kinematics Analysis of Dual-motor Driven Six-legged Upright Walking Mechanism - Zhang Jiulei (Jixie chuandong)
A kind of dual-motor driven walking mechanism which consist of six upright walking legs made up of connecting rods is designed. Firstly,through analyzing the principle of walking leg mechanism,the simple planar four-bar linkage is decomposed by unilateral walking leg mechanism. Based on complex vector method,the kinematical equation is established. According to the kinematics equation,the analysis of the position of the movement,the limit position is find out,the position map of the walking leg mechanism is drawn,the movement space of the walking leg is determined,and whether the interference occurs is judged. Finally,a prototype is built to verify the feasibility of the design scheme. The prototype test results show that walking leg mechanism can meet to working requirements of six-legged walking robot,this design scheme is feasible. The basis for the next optimization design and development of new walking robots is provided,it has important research significance.